2021
DOI: 10.1111/ijd.15891
|View full text |Cite
|
Sign up to set email alerts
|

Spiny keratoderma, a late COVID‐19 manifestation?

Abstract: Metapneumovirus, Bocavirus, Respiratory syncytial virus, Adenovirus, and Enterovirus), but it was found to be negative. Lung involvement was not detected in thoracic tomography. Hydroxyzine (1 mg/kg/day), systemic methylprednisolone (1 mg/ kg/day), and phenyramine (1 mg/kg/day) treatments given for urticaria were thought to be resistant to treatment. Vitamin D (1,000 U/day) was added empirically to the patient's treatment. The patient's fever did not recur. The patient was discharged on the 5th day, after exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…COVID-19 infection has been associated with various dermatologic manifestations including urticarial eruption, pseudo-chilblain, maculopapular rash and vesicular lesions. 1 Recently, a case of new-onset spiny keratoderma in association with COVID-19 has been reported by Dominguez-Santas et al 2 Similar to the case described in this letter, we would like to share our experience with a patient who developed folliculocentric hyperkeratotic papules following mildly symptomatic COVID-19.…”
Section: Lichen Spinulosus Following Covid-19 Infection: Another Poss...supporting
confidence: 69%
See 1 more Smart Citation
“…COVID-19 infection has been associated with various dermatologic manifestations including urticarial eruption, pseudo-chilblain, maculopapular rash and vesicular lesions. 1 Recently, a case of new-onset spiny keratoderma in association with COVID-19 has been reported by Dominguez-Santas et al 2 Similar to the case described in this letter, we would like to share our experience with a patient who developed folliculocentric hyperkeratotic papules following mildly symptomatic COVID-19.…”
Section: Lichen Spinulosus Following Covid-19 Infection: Another Poss...supporting
confidence: 69%
“… 2 In this case, a 68‐year‐old man presented with milimetric, spiny, keratotic papules in both palms 1 month after mild COVID‐19 infection. 2 Similar to our patient, no infectious disease such as HIV and hepatitis, drug or malignancy which would trigger lichen spinulosus, was detected in the case reported by Dominguez‐Santas et al 2 Furthermore, Tammaro et al 10 recently reported a case of severe palmar hyperkeratosis and hematochezia observed in a 85‐year‐old man who had interstitial pneumonia, myocarditis, and severe respiratory failure due to COVID‐19. The severity of cutaneous hyperkeratosis showed correlation with the deterioration of clinical symptoms in this case.…”
mentioning
confidence: 94%
“…Of the 58 articles, 10 were case series, resulting in 84 SpK cases for analysis (Table 1). The individual cases were published in the USA (32), 1,3,8,9,12,16,18,20,24,[30][31][32][33][34]37,45,47,49,53 Spain (12), 14,22,23,26,28,29,36,39,50,54,58 Saudi Arabia (7), 10 Italy (6), 2,13,19,46,55 Japan (6), 11,21,25,40,52 Brazil (4), 5,42 United Kingdom (3), 41,57 Australia…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 41 cases had a reported history of systemic disease-13 with type II diabetes mellitus, 9,25,33,34,38,40,41,43,44,46,56,58 10 with hyperlipidemia, 18,25,39,43,53,55,56 7 with pulmonary disease including COPD and asthma, 7,14,18,21,44,47,52 and 3 with chronic kidney disease. 38,44,56 Other systemic conditions associated with SpK included pulmonary tuberculosis, 14 SARS-CoV-2 infection, 54 protein S deficiency, 5 Darier disease, 17 type IV hyperlipoproteinemia, 19 autosomal dominant polycystic kidney disease, 16 and sarcoidosis. 7 The average reported age was 47.9 in hereditary cases and 63.6 in sporadic cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation